ChemInform Abstract: A Cascade Phosphinoylation/Cyclization/Desulfonylation Process for the Synthesis of 3‐Phosphinoylindoles. Issue 31 (14th July 2016) - Gao, Yuzhen; Lu, Guozhang; Zhang, Pengbo; Zhang, Liangliang; Tang, Guo; Zhao, Yufen
Abstract: A wide range of substrates can be used for this operationally simple cascade annulation process to give 3‐phosphinoylindoles.